2019
DOI: 10.1002/ijc.32681
|View full text |Cite
|
Sign up to set email alerts
|

Should we consider gallbladder cancer a new smoking‐related cancer? A comprehensive meta‐analysis focused on dose–response relationships

Abstract: The few studies on the association of smoking with gallbladder cancer risk have given conflicting results. Here, we provide the most accurate and up-to-date quantification of the effect of cigarette smoking on gallbladder cancer risk, and investigate for the first time the dose-response relationships. Using an innovative approach for the identification of publications, we conducted a systematic review and meta-analysis of epidemiological studies published until March 2019 on the association of smoking with gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…55 A recent meta-analysis found that smokers had a higher risk of GBC compared with nonsmokers (RR=1.33, 95% CI 1.17-1.51). 56 The risk of GBC was linearly correlated with smoking intensity and smoking duration, and the risk of GBC in smokers after quitting smoking did not decrease significantly with increasing smoking cessation time. Certainly, further work is needed to elaborate the relationship between smoking and alcohol consumption and the risk of GBC.…”
Section: Dietary Habitsmentioning
confidence: 82%
“…55 A recent meta-analysis found that smokers had a higher risk of GBC compared with nonsmokers (RR=1.33, 95% CI 1.17-1.51). 56 The risk of GBC was linearly correlated with smoking intensity and smoking duration, and the risk of GBC in smokers after quitting smoking did not decrease significantly with increasing smoking cessation time. Certainly, further work is needed to elaborate the relationship between smoking and alcohol consumption and the risk of GBC.…”
Section: Dietary Habitsmentioning
confidence: 82%
“…4 Of these major cancers listed in tables 1 and 2, while the role of tobacco smoking in lung and head and neck cancers is well-known, the documented contributions of this exposure to increased risks for cancers of the stomach, cervix, breast, ovary, and gallbladder are less highlighted and discussed. [5][6][7][8][9][10] The trends are for decreasing smoking in the last decade (7-11%), but markedly so for women, so part of the lung and other cancer story in women can be from previously much higher rates of smoking. 11,12 The smoking problem is compounded by the preponderance of data indicating that passive smoking-exposure to second-hand smoke-is associated with increased risk of lung and breast cancers.…”
Section: Selected Relevant Descriptive and Analytic Epidemiology For Nepalmentioning
confidence: 99%
“…1 Given the unsuitability of a randomized control trial to answer this question, we must rely on observational evidence. We therefore read with great interest the recent meta-analysis of cigarette smoking and gallbladder cancer risk by Lugo et al 2 This meta-analysis included case-control and cohort studies that provided risk or mortality estimates for either gallbladder cancer alone or biliary tract cancers and gallbladder cancer combined. Lugo et al found that cigarette smoking was positively associated with gallbladder cancer, with a pooled risk for current vs. never smoking across two casecontrol and eight cohort studies of 1.33 (95% CI: 1.17-1.51).…”
mentioning
confidence: 99%
“…The relationship between cigarette smoking and gallbladder cancer risk could be modified by geographical factors.In the analysis by Lugo et al, there was evidence of effect modification by geography. In particular, higher pooled relative risks (RR) for the effect of ever vs never cigarette smoking on gallbladder cancer risk were observed in Asia (RR: 1.43) and North America (RR: 1.52), while the relative risks in Europe (RR: 1.16) and Oceania (RR: 1.00) were modest or null 2. It is plausible that the effect of cigarette smoking on gallbladder cancer risk may differ in the context of other risk factors that are geographically heterogeneous.…”
mentioning
confidence: 99%
See 1 more Smart Citation